2013
DOI: 10.1063/1.4808338
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of lead-free 0.5Ba(Zr0.2Ti0.8)O3-0.5(Ba0.7Ca0.3)TiO3 ceramic

Abstract: Articles you may be interested inSymmetry determination on Pb-free piezoceramic 0.5Ba(Zr0.2Ti0.8)O3-0.5(Ba0.7Ca0.3)TiO3 using convergent beam electron diffraction method J. Appl. Phys. 115, 054108 (2014) Temperature dependent dielectric permittivity studies demonstrated frequency independent behavior, indicating that the studied sample was not a typical relaxor ferroelectric. A polymorphic phase transition between rhombohedral and tetragonal phase was noticed near room temperature followed by a tetragonal to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
63
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 46 publications
(51 reference statements)
9
63
2
Order By: Relevance
“…21 Detailed procedure of the samples preparation and their structural characterization can be found elsewhere. 20 The grain size in the BCZT samples was in the range from 4 to18 lm. Ceramic pellets were polished to optical quality by using diamond paste and cleaned in alcohol and acetone afterwards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Detailed procedure of the samples preparation and their structural characterization can be found elsewhere. 20 The grain size in the BCZT samples was in the range from 4 to18 lm. Ceramic pellets were polished to optical quality by using diamond paste and cleaned in alcohol and acetone afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that ferroelectric domains become miniaturized down to a nanometer size with apparent domain hierarchy that is coincident with the d 33 -maximum region on the phase diagram. First Piezoresponse Force Microscopy (PFM) study 20 revealed a complex mosaic-like domain structure with sub-lm domain periodicity and clear nanoscale polarization switching as documented by the nanoscale piezoresponse hysteresis loops. This work is focused on further study of the 50 BZT 50BCT lead-free system using nanoscale piezoelectric methods.…”
Section: Introductionmentioning
confidence: 99%
“…Among lead free electro-ceramics with good dielectric and ferro/piezo electric properties, the 0.5Ba(Zr 0.2 Ti 0.8 )O 3 -0.5(Ba 0.7 Ca 0.3 )TiO 3 is the most promising binary system for the substitution of commonly commercial PZT [1][2][3] . As an example, Liu et al 4 reported a high piezoelectric coefficient d 33 ~690 pC/N for this binary composition.…”
Section: Introductionmentioning
confidence: 99%
“…337 The compositional range of BZT-BCT for actuator applications (red blurred shaded area) comprises pseudocubic materials with weak relaxor features. 338,339 Nevertheless, detailed XRD experiments were able to reveal the average atomic structure of the system. 331,333 It must be pointed out, however, that the short-range structure of the BZT-BCT differs from its long-range order similarly as in relaxor materials.…”
Section: Atomic Structurementioning
confidence: 99%